Development of a small scale thermoelectric generator integrated with a waste oil stove - Muhammad Iwan; Gunarto Gunarto; Lani Lani; Apri Rahmadi; Mursalin Mursalin; Eko Julianto (Politeknik Negeri Lhokseumawe, 2025)
The growing accumulation of used motor oil, classified as hazardous waste (B3), presents an urgent environmental challenge. This research investigates the feasibility of generating small-scale electrical power using waste oil combustion in a stove integrated with a Thermoelectric Generator (TEG). An experimental setup was developed where the hot side of the TEG is heated by the combustion chamber of the stove and the cold side is cooled using a water block. Real-time temperature, voltage, and power output data were collected using an Arduino-based sensor system. The maximum observed temperature difference across the TEG module was 233 °C. Under open-circuit conditions, a peak voltage of 37.32 V was recorded, while the maximum output power under load reached 11.72 W at a current of 0.76 A. The system achieved its highest electrical efficiency of 0.182% at the peak temperature gradient. These results demonstrate the potential of TEG modules for converting heat from waste oil combustion into electricity, with optimal performance achieved under stable high-temperature gradients and consistent fuel supply.